THE PHENOMENA OF COLLECTIVE LEXICAL ASSOCIATIONS IN A PARTONYMIC AND HYPONYMIC RELATIONSHIP IN CHILDREN'S SPEECH (Neo Scientific Peer Reviewed Journal, 2023)
The article talks about the expression of partonymic and hyponymic lexical associations in the speech of preschool children, the specific features of associative units in this context. Also, some factors that create partonymic and hyponymic lexical associations in the speech of preschool children are discussed.